2019
DOI: 10.1200/jco.2019.37.15_suppl.8531
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of neoadjuvant PD-1 blockade with sintilimab in resectable squamous non-small cell lung cancer (sqNSCLC).

Abstract: 8531 Background: NSCLC patients who have potentially resectable disease often subsequently relapse after surgery. New therapy that prevents relapse after surgery is desperately needed. In this study, we tested the efficacy and safety of neoadjuvant sintilimab, an anti-PD-1 antibody, for patients with resectable sqNSCLC in China. Methods: All patients had treatment-naïve resectable sqNSCLC (stage IB-IIIA) that was confirmed by histopathology. Patients received two cycles of sintilimab (200 mg IV) on Day 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In this study, there is a positive correlation between the patient's SLD reduction rate and the pathological remission rate (r=0.565, P=0.012), but no apparent correlation between the changes of LSD reduction rate and SLD reduction rate (r=0.393, P=0.096) and the pathological remission rate (r=0.262, P=0.278). In the past reports, the patient's SLD reduction rate and the pathological remission rate have always been related to the trend, including lung cancer (30), etc. This may be because the esophagus, as an organ of the digestive tract, has strong peristalsis and contraction movement, and due to the scraping of the food during the eating process, the necrotic cancer tissue is peeled off into the stomach so that its changes can be observed on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there is a positive correlation between the patient's SLD reduction rate and the pathological remission rate (r=0.565, P=0.012), but no apparent correlation between the changes of LSD reduction rate and SLD reduction rate (r=0.393, P=0.096) and the pathological remission rate (r=0.262, P=0.278). In the past reports, the patient's SLD reduction rate and the pathological remission rate have always been related to the trend, including lung cancer (30), etc. This may be because the esophagus, as an organ of the digestive tract, has strong peristalsis and contraction movement, and due to the scraping of the food during the eating process, the necrotic cancer tissue is peeled off into the stomach so that its changes can be observed on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment-related AEs were reported in 4 patients (18.2%), mainly grade 1 or 2. In addition, the authors reported that a decrease in standardized uptake values (SUV) on positron emission tomography/computed tomography (PET/CT) imaging prior to surgery compared to baseline, may be predictive for pathological response [ 25 ].…”
Section: Neoadjuvant Immunotherapymentioning
confidence: 99%
“…However, pathological assessment by re-biopsy is not always feasible in advanced NSCLC and the discrimination between CR and PR thus becomes a new challenge among patients with OMD treated with ICI. Although in early stage some studies have reported a correlation between the decrease in SUV in a fluodeoxyglucose positron emission tomography (FDG-PET) scan as a predictive for pathological response (69), in other trials such as the PRINCEPS trial, the metabolic response could not be correlated with pathological regression (70). Therefore, the correlation between metabolic and pathologic regression merits further prospective evaluation.…”
Section: Optimal Duration Of Treatment Monitoring Of Patientsmentioning
confidence: 99%